FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERNIKAHAN USIA DINI PADA REMAJA PUTRI DI KECAMATAN TANJUNG REJO PERCUT - Mestika Lumbantoruan; Rinawati Sembiring; Rotua Simanjuntak (Jurnal Reproductive Health, 2017)
The early-age marriage is a marriage which done under reproductive age, <20 years old. Riskesdas (2013) stated that among the women at 10 – 54 years old, 2,6 % got married before 15 years old and 23,9 % at 15-19 years old. Based on the data from Religious Affairs Office (Kantor Urusan Agama) in Kecamatan Tanjung Rejo Percut Sei Tuan, there were 83 teenage girls got married at <20 years old in 2016. The purpose of this study is to identify the factors which have correlation with early-age marriage on teenage girls in Kecamatan Tanjung Rejo Percut Sei Tuan in 2017. This is an analytic study with Case Control design. The case group was all of the 45 teenage girls who got married at early age. The control group was taken based on inclusion and exclusion criteria with comparison (1:2) between 90 teenage girls from the case group. The variables were knowledge, education, job, economic status, parents’ role, culture, promiscuity and mass media. The analysis was done in some steps; include univariate, bivariate analysis used Chi Square test, and multivariate analysis with logistic regressing test. The results for every variables are; knowledge (p=0,0005), education (p=0,0005), jobs (p=0,0005), economic status (p=0,003), parents’ role (p=0,270), culture (p=0,001), promiscuity (p=0,001) and mass media (p=0,045), and the multivariate analysis showed that knowledge has p=0,001; OR= 5,082 (95% CI; 1,88113,732). It can be concluded that there is no correlation between parents’ role and early-age marriage, and there are some correlations between knowledge, education, jobs, economic status, culture, promiscuity and mass media with early-age marriage, and the dominant factor is knowledge. It is suggested for government who lead Kecamatan Tanjung Rejo Percut Sei Tuan to cooperative with BKKBN in giving information and education for teenagers and parents about the effects of early-age marriage; and if they have some knowledge, early-age marriage can be decreased then